2003
DOI: 10.1128/jcm.41.7.3001-3006.2003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Methicillin-ResistantStaphylococcus aureusStrains Causing Neonatal Toxic Shock Syndrome-Like Exanthematous Disease in Neonatal and Perinatal Wards

Abstract: Neonatal toxic shock syndrome-like exanthematous disease (NTED) is a new neonatal disease caused by toxic shock syndrome toxin 1 (TSST-1). We conducted a prospective surveillance study and characterized the methicillin-resistant Staphylococcus aureus (MRSA) strains isolated from patients with NTED and compared them with the strains from patients with other MRSA infections and asymptomatic carriers. The study was performed in the neonatal intensive care unit and a general neonatal and maternal ward in the Tokyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 41 publications
0
48
0
1
Order By: Relevance
“…Although Collery et al (34) reported that strains possessing the tst gene are often associated with agr type III, none of our agr type III strains harbored the tst gene. This is important because the tst gene encodes for toxic shock syndrome toxins, causing neonatal toxic shock syndromelike exanthematous disease and staphylococcal purpura fulminans (30,35).…”
Section: Discussionmentioning
confidence: 99%
“…Although Collery et al (34) reported that strains possessing the tst gene are often associated with agr type III, none of our agr type III strains harbored the tst gene. This is important because the tst gene encodes for toxic shock syndrome toxins, causing neonatal toxic shock syndromelike exanthematous disease and staphylococcal purpura fulminans (30,35).…”
Section: Discussionmentioning
confidence: 99%
“…Toxic shock syndrome toxin-1 (encoded by tst) that causes neonatal toxic shock syndrome-like exanthematous disease and Staphylococcal purpura fulminans [25,26] was detected in five community and one clinical strain.…”
Section: Prevalence Of Virulence Genes Among Mssa Strainsmentioning
confidence: 99%
“…A single colony was suspended to a McFarland 1.0 standard in 100 l of TE buffer (20 mM Tris, 2 mM EDTA [pH 7.5]) with 10 U of achromopeptidase (Wako Chemical, Co., Ltd., Osaka, Japan), and the suspension was incubated at 55°C for 10 min. After centrifugation at 18,500 ϫ g for 5 min, the supernatants were used as crude DNA extracts for PCR (22).…”
Section: Methodsmentioning
confidence: 99%